Teacher competence in the implementation of school based oral English assessment / Siti Azura Juih - Juih, Siti Azura (2011)
School Based Oral English Assessment (SBOEA) has brought an impact in the role of English teachers. Since 2003, English teachers are to be accountable to implement SBOEA during classroom instructions and to assess student oral skills according to its standard process and procedure provided by the Malaysian Examination Syndicate (MES). However, the competence of the English teacher to cany out SBOEA in their daily classroom instructions has to be investigated. Therefore, this study aims to examine teacher competence in the implementation of SBOEA. A total of forty-eight Form 4 and Form 5 English teachers of eight secondary schools in Kola Samarahan division involved in the study. This descriptive study employed a set of questionnaire in obtaining data. There are two types of analyses used in this study such as descriptive analysis of frequencies and percentages; and inferential analyses of independent samples ttest and AN OVA. Data analysis produced the following results: 1) Teachers possess a high competence level in the implementation of SBOEA. 2) The first hypothesis failed to be rejected because there were no significant differences in means of the teacher competence level among English teachers from different schools; 3) The second hypothesis was rejected because there were significant differences in means according to teaching experience years and; 4) The third hypothesis was rejected because there were significant differences in means between teachers who attended and not attended the SBOEA course. The results have indicated that most of English teachers in Kota Samarahan possess a high level of teacher competence in the implementation of SBOEA even though there exist some significant differences in terms of teaching experience and; between teachers who attended and not attended the SBOEA course. Thus, this study indicates that these groups of English teachers are competent in implementing SBOEA and able to assess students in SBOEA objectively.